Changing Trends in Oesophageal Endoscopy: A Systematic Review of Transnasal Oesophagoscopy. (1st August 2013) - Sabirin, Junainah; Abd Rahman, Maharita; Rajan, Philip
Abstract : The safety, efficacy, and economic implications of using transnasal oesophagoscopy (TNE) are compared with conventional rigid or flexible oesophagoscopy for oesophageal disorders in otorhinolaryngology (ORL) clinics in this systematic review. Eleven electronic databases were searched for articles on transnasal oesophagoscopy. A total of 67 relevant titles were identified and 39 abstracts were screened of which 17 full- text articles were included in this report. There was fair level of evidence to suggest that TNE was effective for screening examination in patients with dysphagia, globus pharyngeus, and reflux symptoms and for detection of metachronous oesophageal carcinoma. TNE can also be used to biopsy suspicious lesions in the upper aerodigestive tract, placement of wireless pH capsule, transnasal balloon dilation of the oesophagus, secondary tracheoesophageal puncture, and management of foreign bodies. TNE was well tolerated and can be safely performed in an office setting with topical anaesthesia. Complications associated with TNE were mild and uncommon. There was evidence to suggest potential cost savings by performing TNE in the office setting compared with conventional investigation and examination for dysphagia. TNE may lead to a change in practice from investigation and treatment in the operating theatre or day care center to an office-based practice.